Aqueous Nanoparticles: Control of Shell Morphology in p–n Heterostructured Water‐Processable Semiconductor Colloids: Toward Extremely Efficient Charge Separation (Small 2/2019). Issue 2 (11th January 2019) - Kim, Yu Jin; Schaller, Richard D.; Fry, Harry Christopher
Abstract : In article number1803563, Yu Jin Kim and co‐workers report a method to control the structure of shell particles composed of PC60 surfactant and PC61 BM semiconductor via one‐ and two‐phase methodology in water‐borne core–shell nanoparticles (NPs). The NPs exhibit shell morphology‐dependent photonic particle activity, and they show ultra‐fast charge separation and stable property compared with single PC60 micelle‐covered colloids. This work confirms the importance of controlling shell morphology and guides a new protocol for heterostructured water‐processable NPs.